2003
DOI: 10.1046/j.1440-172x.2003.t01-1-00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of Caesarean section and vaginal birth after Caesarian: A Birthrites initiative

Abstract: This paper reports the findings of a small pilot study undertaken to identify women's perceptions of their Caesarean section and/or their experience of attempting to achieve a vaginal birth after Caesarean. Fifty-nine women replied to a survey designed and distributed by the consumer organisation Birthrites. The survey consisted of 22 closed and open-ended questions. Descriptive statistics and content analysis were used to analyse the data. Six major factors that impacted on women's perceptions of their birthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Previous studies have shown that women have a strong preference for adequate and unbiased information regarding their care in pregnancy. 9 This study agrees with that finding. It is important that antenatal caregivers provide adequate information and counselling to women, as this will probably improve the acceptance of caesarean section.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that women have a strong preference for adequate and unbiased information regarding their care in pregnancy. 9 This study agrees with that finding. It is important that antenatal caregivers provide adequate information and counselling to women, as this will probably improve the acceptance of caesarean section.…”
Section: Discussionsupporting
confidence: 92%
“…Although maternal desire to achieve vaginal delivery and perception of caesarean section as a sign of reproductive failure is not peculiar to Nigerian women, 9 this study suggests that there may be serious implications to these in the Nigerian context. While women with such feelings in developed countries usually accept caesarean sections when indicated, the opposite seems to apply to Nigerian women.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, this could be one reason for the newly evolved psychiatric terminology, "tokophobia," used to describe the fear and anxiety some women experience surrounding childbirth. 26 Fenwick et al 27 surveyed 59 women in Australia and North America about their perceptions of their birth experience after having a cesarean birth. All participants were members of an organization that supports consumer information about cesarean birth.…”
Section: Role Of Languagementioning
confidence: 99%
“…To this end, maternity hospitals need to reexamine how best to provide care in a subsequent pregnancy. Policies and procedures for women having a VBAC should reflect the best available evidence and move away from inflexible, restrictive, and detrimental practices (Fenwick, Gamble, & Mawson, 2003). Women with a history of a CS should be able to access noninterventionist environments such as birth centers and midwifery continuity of care models.…”
Section: Repeat Cesarean Section Versus Vaginal Birth After Cesareanmentioning
confidence: 99%